2008
DOI: 10.1158/1535-7163.mct-08-0388
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD30 diabody-drug conjugates with potent antitumor activity

Abstract: Anti-CD30 diabodies were engineered with two cysteine mutations for site-specific drug conjugation in each chain of these homodimeric antibody fragments. Diabodies were conjugated with f4 equivalents of the anti-tubulin drugs, monomethyl auristatin E or F, via a protease-cleavable dipeptide linker, to create the conjugates, diabody-vcE4 and diabody-vcF4, respectively. Diabody conjugation had only minor (<3-fold) effects on antigen binding. DiabodyvcF4 was potently cytotoxic against the antigen-positive cell li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 36 publications
0
67
0
1
Order By: Relevance
“…UV/vis spectroscopy is the most commonly implemented technique to determine DAR. This molar ratio can be derived from the Beer-Lambert law by comparing the IgG absorbance maxima at 280 nm to that of a drug molecule in simultaneous equations (34,67,(71)(72)(73)(74). ADCs with a variety of payloads have been evaluated using this method, including DM1, methotrexate, calicheamicin analogues, and auristatins (11,75,76).…”
Section: Uv/vismentioning
confidence: 99%
“…UV/vis spectroscopy is the most commonly implemented technique to determine DAR. This molar ratio can be derived from the Beer-Lambert law by comparing the IgG absorbance maxima at 280 nm to that of a drug molecule in simultaneous equations (34,67,(71)(72)(73)(74). ADCs with a variety of payloads have been evaluated using this method, including DM1, methotrexate, calicheamicin analogues, and auristatins (11,75,76).…”
Section: Uv/vismentioning
confidence: 99%
“…As a case in point, preclinical studies with anti-CD30 diabodies conjugated to auristatin demonstrated efficacy in preclinical tumor models (83). However, whether such approaches yield improved tumor penetration and hence enhanced clinical responses in patients remains to be seen.…”
Section: Barriers To Effective Tumor Penetrationmentioning
confidence: 99%
“…Tumor targeting by the anti-CD70 mAb h1F6 C4v2 showed substantial accumulation in CD70-positive tumor xenografts. The peak mAb concentration of 40.9 Ϯ 9.7% ID/g was achieved 1 day after dose, a very high value for tumor targeting by mAbs (Ferl et al, 2006;Cai et al, 2007;Kim et al, 2008;SmithJones et al, 2008). Serum drug-linker stability measurements indicate that about half the drug is lost from the ADC during the 10-day period, which is considerably longer than the circulating half-life of the conjugate.…”
Section: Discussionmentioning
confidence: 95%